Relationship Model Analysis of Personal Factors, Celebrity Endorsement, Buying Behavior, and Word of Mouth on Tourists on Komodo Island - Ramdhan Kurniawan; Usep Suhud; Fauzy Rahman Kosasih; Zulmi Ramdani (Jurnal Perspektif, 2023)
The purpose of this study was to analyze factors affecting word of mouth. A causality quantitative research design was used to answer this question by involving a sample of 120 tourists on Komodo Island who were selected using a purposive sampling technique. A modified set of questionnaires was distributed to all respondents, including informed consent as involvement in the study, and then analyzed using multiple regression tests and mediation tests with the help of AMOS software. The study results show that personal factors and celebrity endorsements have a partial effect on buying behavior, as well as buying behavior which significantly affects the word of mouth of research respondents. Personal factors and celebrity endorsements also directly affect word of mouth. The implications of this research provide information about the importance of these variables in supporting the optimization of tourism on Komodo Island.